NOVELTIES IN ALYSICARPUS DESV. (FABACEAE) - POKLE, D. S. (REINWARDTIA, 1999)
Two new species and two new varieties in the genus Alysicarpus Desv. (Fabaceae) are described. All the new taxa are collected from various parts of Maharashtra. A note on their distribution throughout India is also added.